Dietary Patterns of Women in Relation to Risk of Over- and Underweight in Nepal (P10-056-19). (13th June 2019) - Thorne-Lyman, Andrew; KC, Angela; Manohar, Swetha; Shrestha, Binod; Klemm, Rolf D W; Webb, Patrick; West, Keith P
Abstract: Objectives: This study describes dietary patterns of women in Nepal and how dietary patterns vary by under-and-overweight, socioeconomic status (SES), and agro-ecological zone. Methods: In 2016, a national mid-year nutrition and health survey was conducted in Nepal. In each zone (mountains, hills and Tarai) 7 sub-districts (village development communities, VDCs) were systematically selected after a random start (N = 21). Within each VDC, 3/9 wards (N = 63) were sampled in proportion to population and all households were enumerated. In all, 5380 women, married <2 years or having >1 child <72 mo of age, were assessed for weight, height, caste, SES, & food security among other factors. Diet was assessed by a 7-day food frequency questionnaire with 48 items. Latent class analysis was used to generate dietary patterns, consolidated into 12 food groups. Goodness-of-fit indicators supported a 7 class (dietary pattern) model. Chi 2 tests were used to test statistically significant differences in dietary patterns by characteristics. Results: National median [IQR] intake frequencies for key foods by women were: fruits 3 [1, 7], vegetables 12 [7, 20], meat 1 [0.3], eggs 0 [0, 1], and dairy 6 [ 0, 14]. Only 10% of women consumed fruits or vegetables 5 times per week. Dietary patterns (% of women) identified included: 1) Most diverse (18%); 2) Diverse no egg no alcohol (17%); 3) Diverse orange fruit, veg and milk (4%); 4) Moderate (13%); 5) Non-diverse meat and alcohol (10%); 6) Low moderate diversity with oil and fat (22%); and 7) Monotonous (17%). Patterns 2 and 6 were distinct of the Tarai and pattern 3 more evident in the Hills. Significant variation was evident by wealth quintile, food security status, caste, zone, and body mass index (BMI). Women whose intakes aligned with Pattern 1 had the highest prevalence of BMI >25.0 kg/m 2 (26.7%) and those eating pattern 3, the lowest (1.4%). Pattern 1 had the lowest prevalence of BMI <18.5 kg/m 2 (12.6%), and pattern 6 the highest (28.8%). Conclusions: Dietary patterns of women in Nepal are heterogeneous, vary by SES, agro-ecological and cultural factors, and are associated with risk of over and underweight. Funding Sources: Supported by USAID through the Feed the Future Nutrition Innovation Lab, with additional assistance from Sight and Life and the Bill & Melinda Gates Foundation.